Capital Controls, Liberalizations, and Foreign Direct Investment - Desai, Mihir A.; Foley, C. Fritz; Hines, James R. (Review of Financial Studies, 2006)
This article evaluates the impact of capital controls and their liberalization on the activities of US multinational firms. These firms attempt to circumvent capital controls by reducing reported local profitability and increasing the frequency of dividend repatriations. As a result, the reported profit impact of local capital controls is comparable with the effect of 27% higher corporate tax rates, and affiliates located in countries imposing capital controls are 9.8% more likely than other affiliates to remit dividends to parent companies. Multinational affiliates located in countries with capital controls face 5.25% higher interest rates on local borrowing than do affiliates of the same parent borrowing locally in countries without capital controls. Capital control liberalizations are associated with significant increases in multinational activity-property, plant, and equipment grow at 6.9% faster annual rates following liberalizations. The combination of the costliness of avoidance and higher interest rates discourages investment in countries with capital controls, and this effect is reversed upon liberalization of controls.